Association of Procalcitonin with the Patient's Infection Characteristics and Prognosis after Hematopoietic Stem Cell Transplantation. (13th September 2022) - Li, Shan-Shan; Gu, Jun-xu; Li, Xiao-wei; Zhang, Na; Jia, Mei; Pei, Lin; Su, Ming
Abstract : Objective . To study whether procalcitonin (PCT) is an important indicator of infection with or without agranulocytosis and to reveal whether PCT can distinguish between infected sites and affect prognosis after hematopoietic stem cell transplantation (HSCT). Method . In the present study, 682 patients with HSCT were enrolled, and their clinical characteristics were noted. Their blood culture and inflammatory and biochemical indicators were studied. The patients were divided into respective groups according to the degree of agranulocytosis, type of bacterial infection, infected sites, and prognosis. Results . The PCT, CRP, and D-dimer levels were significantly improved in patients with positive blood culture results compared to the case for those with negative blood culture results. The PCT level was the highest in the gram-negative group. The levels of PCT and D-dimer were significantly elevated in patients with infection and agranulocytosis after HSCT compared to those in the nonagranulocytosis cohort. Interestingly, no significant difference in the PCT level was observed among any of the eight foci. Lower PCT levels were associated with higher survival in patients with infection after HSCT. Conclusion . Among patients that underwent HSCT, PCT levels were significantly elevated in those with infection and agranulocytosis, with the levels being specifically high in the gram-negative group. Moreover, lower PCT levels were associated with higher survival in patients with infection after HSCT.